Pengembangan Desain Pembelajaran PAI untuk Meningkatkan Keterampilan Pengajaran Calon Guru Madrasah - Rizki Amelia Siregar; Lannita Siregar; Gusmaneli Gusmaneli (Journal Educational Research and Development | E-ISSN : 3063-9158, 2025)
This research examines the development of Islamic Religious Education (PAI) instructional design for prospective madrasah teachers through four main stages: needs analysis, design principles and models, implementation, and impact evaluation. The study results indicate a gap between mastery of religious theory and pedagogical skills, which requires contextual needs analysis based on local data. Effective instructional design principles include an integrative approach, student-centeredness, contextualization for the digital era, and adaptability to student diversity. Design models such as ADDIE, CTL, and differentiated learning are considered relevant for developing 21st-century competencies. Implementation is carried out through microteaching, project-based learning, and the use of digital technology to enhance the creativity and reflection of prospective teachers. Formative and summative evaluations are used to assess improvements in teaching skills, professionalism, and internalization of Islamic values. Overall, integrated and reflective PAI instructional design can produce prospective madrasah teachers who are adaptive, have character, and are competent in facing the challenges of modern education.